PERBANDINGAN PROFITABILITAS PASIEN BPJS DAN PASIEN UMUM DI RUMAH SAKIT BRAWIJAYA SURABAYA DENGAN PENDEKATAN CUSTOMER PROFITABILITY ANALYSIS - Muhammad Saiful Hakim; Aldhilla Isti Nuswandari; Nugroho Priyo Negoro (JURNAL SOSIAL HUMANIORA (JSH), 2016)
Since 2013 Indonesia has developed their national healthcare programme (JKN) that run by BPJS kesehatan. Nowadays  this system has attract broad demand in Indonesia. This programme used INA CBG system as their payment system for the healthcare. Since the implementation many of hospital has doubt regard this system has provided hospital with profit. This paper answer the question by using Customer Profitability analysis that extracted from Activity Based Costing Measurement to measuring profitability between BPJS patient and regular patient . The result indicated that for short term, BPJS Patient generated higher profit rather than regular patient. On the other hand for long term BPJS patient have lower profit compared with regular patient